Perceptions and Insights of Ibn Al ‘Irāqī in "Toḥfah Al Taḥṣīl" on Al-‘Ala’ī’s Book "Jāmi’ Al Taḥṣīl" - Nafiz Husain Hammad (Journal of Islamic and Religious Studies, 2020)
The research reveals significant insights cited by Ibn Al ‘Irāqī in his book "Toḥfah Al Taḥṣīl" on the illusions of Al-‘Alā'ī in his book "Jāmi Al Taḥṣīl". It highlights the scientific value of those illusions that Ibn Al-‘Irāqī pointed out. Several of them are related to narrators of hadith and their issues of hearing from their sheikhs. Many of those illusions are related to the chain narrators (isnad), the main text of the report (matn), or their position in the books of sunnah. There are no previous studies on this subject. I put the sequential insights I revel under headlines through which one can realize the illusions that Al-Ala'i fell in. I conclude with the perceptions that both Ibn Al-‘Iraqī and Al-‘Alā’ī have shared. I don’t mention my opinion after each insight for Ibn Al-‘Iraqī; however, my silence is an approval to what he said. When I went against him or it was important to mention any comment or information, I openly said my opinion and explained the reasons for my opposition. Some of the research findings are: Al-Ala'i ignores mentioning the narrator's gap (irsal), although Al-Mizzī mentions it in his book "Tahdhīb", or the scholars mention it before both of them. He describes the narrator having a gap (irsāl) and attributes it to Al-Mizzī. He added notes like "he didn't encounter him" and formulated expressions that weren’t mentioned by neither Al Dhahabī nor Al-Mizzī. He references a Ḥadīth to a book that it is not included in.